Screening for atrial fibrillation in primary care. Issue 1 (1st January 1998) - Wheeldon, N M; Tayler, D I; Anagnostou, E; Cook, D; Wales, C; Oakley, G D G
Abstract : Objective: To investigate a population of elderly people for atrial fibrillation and to determine how many of the cases identified might benefit from treatment with anticoagulants. Methods: From a practice of four primary care physicians, 1422 patients aged 65 years and over were identified, of whom 1207 (85% of the total population) underwent electrocardiographic screening to detect the presence of atrial fibrillation. Patients with the arrhythmia were further evaluated by echocardiography and interview, to stratify their risk of stroke based on echocardiographic and clinical risk factors, their perceived risk from anticoagulation, and their attitude towards this treatment. Their primary care physician was also interviewed to determine the factors influencing the prescription of anticoagulants. Results: The arrhythmia occurred in 65 patients (5.4% overall), its prevalence increasing markedly with age (2.3% in 65 to 69 years age group; 8.1% in those over 85). Warfarin was being prescribed to 21.4% of these patients, although the findings of the study indicate that a further 20% were eligible for this treatment. Symptoms suggestive of cardiac failure were common (32.1%) and coexisting pathology was often identified by cardiac ultrasound in these patients (left ventricular hypertrophy, 32.1%; impaired left ventricular contractility, 21.4%; left atrial dilatation, 80.4%; mitral annular calcification, 42.9%; mitral stenosis, 7.1%; mitral regurgitation, 48.2%; aortic stenosis, 8.9%). In all but one case, the decision to anticoagulate was based on the clinical rather than the echocardiographic findings. Conclusions: Individual risk–benefit assessment in elderly patients with atrial fibrillation suggests that almost half (41.4%) are eligible for full anticoagulation with warfarin, whereas presently only one fifth are receiving this treatment. The decision to anticoagulate can be made on clinical grounds in most cases. If these results are confirmed, a doubling of the current number of patients taking anticoagulants can be anticipated.